Social Capital, Family Support, Behavior Use of Personal Protective Equipment (PPE) as the Alternative to Improve the Performance of Employees Exposed to High Intensity Noise - Budi Yulianto; Bambang Sunarko; Nurlailis Saadah; Uswatun Khasanah (Journal of Global Pharma Technology, 2020)
Introduction: Many previous studies have shown that noise intensity in weaving of the textile industry exceeds TLV (> 85dBA) which is difficult to avoid and impossible to reduce. Employees who are exposed to noise and do not use PPE with a long duration of exposure will get an effect in terms of both physical and psychological health. This results in a decline in their performance. This study aims to examine the social aspects of the workplace (social capital), social aspects of the family (family support), and the attitude of employees towards PPE to the performance of those working in weaving exposed to high intensity noise for a long time through work stress. Methods: This study used an observational analytic design with a cross-sectional approach. The location of this research was the textile industry of PT Dan Liris in Banaran, Grogol, Sukoharjo, Central Java. The population of this study was 343 employees working in the weaving department of PT Dan Liris, who met the criteria. The sample size was 170, taken by proportional simple random sampling technique. Exogenous variables in this study included: social capital, family support, employee attitudes toward PPE, and work stress. Endogenous variables in this study included: employee performance, social capital variables, family support, employee attitude towards PPE, work stress, and performance which were measured using a questionnaire. The data were analyzed using path analysis. Results: There was a positive direct effect between social capital and employee attitudes towards PPE on employee performance, meaning that the social environment of employees who had good social capital could improve their performance by 0.085 points. In addition, good employee attitude towards PPEcould also improve their performance by 0.376 points. Keywords: Social capital, Employee Attitude towards PPE, Performance